The role of transformational leadership, job demands and job resources for patient safety culture in Norwegian nursing homes: a cross-sectional study - Camilla Seljemo; Petter Viksveen; Eline Ree (BMC, 2020)
Abstract Background Transformational leadership style is considered to be of importance to increase patient safety, to facilitate a balance between job resources and job demands, and to create a sound patient safety culture within health care services. However, there is limited research assessing these associations within the context of nursing homes. The aim of this study was to assess the association between transformational leadership, job demands and job resources; and patient safety culture and employees' overall perception of patient safety in nursing homes. Method A cross-sectional survey of employees in four Norwegian nursing homes was conducted (N = 165). Multiple hierarchical regression analysis was used to assess the explained variance of transformational leadership, job demands and job resources on patient safety culture and overall perception of patient safety. Results Transformational leadership explained 47.2% of the variance in patient safety culture and 25.4% of overall perception of patient safety, controlling for age and gender (p < 0.001). Additionally, job demands and job resources explained 7.8% of patient safety culture and 4.7% of overall perception of patient safety (p < 0.001). Conclusion Implementing transformational leadership style may be important in creating and sustaining sound patient safety culture in nursing homes. Furthermore, leaders should make an effort to facilitate a good work environment with an optimal balance between job demands and job resources, as this in turn might have a positive influence on patient safety culture.